EFEK PANDEMI COVID-19 TERHADAP PEMBELAJARAN PAI DI SMP NEGERI 2 JOGOROTO - Solikhin, Solikhin; Khulailiyah, Ahsanatul; Abdul Hafid Dasuqi, Muhammad; Khoirur Rozikin, Hari (ILJ: Islamic Learning Journal, 2023)
The world of education is one of the sectors affected by the Covid-19 phenomenon. Educators and students experience many difficulties and require them to fight these challenges. This study aims to reveal the impact of the Covid-19 phenomenon on learning Islamic religious education at SMPN 2 Jogoroto Jombang and how educators try to overcome the various negative impacts it causes. Research uses descriptive qualitative research methods with data collection methods of interviews, observation, documentation and uses analysis in accordance with qualitative methods. The Covid-19 phenomenon has had several impacts, including limited facilities and infrastructure in implementing learning, including cellphones, computers, laptops, internet quota. Internet networks are still difficult to access and educators are not flexible in conveying material and monitoring the overall growth and development of children. Online learning accelerates the transformation in digitization. the online learning system is a technology-based learning system which certainly requires educational institutions, both from educators, students, and even parents. The professionalism of PAI teachers at SMP Negeri 2 Jogoroto in generating new ideas to find creativity and present a more effective and efficient learning process. Acceleration of PAI Teachers in the use of online learning applications. Technological transformation creates various online learning program platforms such as Google Meet, Zoom Meeting which can support PAI learning. The internet as a source of positive information in PAI learning at SMP Negeri 2 Jogoroto